2021
DOI: 10.1111/jce.15135
|View full text |Cite
|
Sign up to set email alerts
|

Local impedance‐guided radiofrequency ablation with standard and high power: Results of a preclinical investigation

Abstract: are salaried employees of Boston Scientific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…A recent animal study by Osei et al 52 demonstrated improved procedural and ablation times and increased ability to achieve target LI drops (15–40 Ω) with a higher power (50 W) shorter duration approach. A total of 50 W power delivery using CF‐LI catheter is supported by preliminary data from a human observational study of first‐time PVI with CF guidance, reporting an impressively short procedure duration of only 46.5 ± 10.4 min and RF delivery time of 13.5 ± 4.3 min 50 .…”
Section: Local Impedance—the New Kid On the Blockmentioning
confidence: 99%
“…A recent animal study by Osei et al 52 demonstrated improved procedural and ablation times and increased ability to achieve target LI drops (15–40 Ω) with a higher power (50 W) shorter duration approach. A total of 50 W power delivery using CF‐LI catheter is supported by preliminary data from a human observational study of first‐time PVI with CF guidance, reporting an impressively short procedure duration of only 46.5 ± 10.4 min and RF delivery time of 13.5 ± 4.3 min 50 .…”
Section: Local Impedance—the New Kid On the Blockmentioning
confidence: 99%
“…However, since a thermal feedback system can hardly be installed in the SE, the temperature in the RF-ablated esophagus was continuously recorded using a thermal camera instead. Moreover, as other studies have reported that the tissue temperature rises, ion mobility within the heated tissue increases, causing a higher current flow and a lower impedance, it could be a specific marker of local tissue heating at a given target site during the RF ablation procedure [26][27][28] . Therefore, it could be expected that a certain ablation region would be achieved despite the absence of a thermal feedback system, since the difference in impedance during the RF ablation time was not large as 10-30 Ω in our current study [29][30][31] .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have used pig models to test different innovative ablation technologies such as the laser-balloon, the low-intensity collimated ultrasound system, the diamond tip ablation catheter, impedance-guided ablations and the different pulsed field ablation catheter (9)(10)(11)(12)(13)(14)(15)(16). All of these studies investigated single ablation lesions without the specific goal of achieving complete pulmonary vein isolation.…”
Section: Discussionmentioning
confidence: 99%